Optimizing Location for Downstream Industry on Remote Island Products - N, Zulkifli; Azry, Said Maulana (SAFE-Network, 2025)
This research aims to select the most optimal and efficient location for frozen banana fritter production to support efforts in optimizing downstreaming of leading commodity industries of Kepulauan Mentawai Regency. The research evaluates potential sites in Padang City and Kepulauan Mentawai Regency, employing the Economic Analysis method with the Brown-Gibson model, combining quantitative and qualitative approaches. Factors influencing frozen banana fritter production and site selection are examined through market surveys and interviews with relevant experts and stakeholders. The findings highlight Padang City as the ideal production site. This research holds significance in enhancing the local economy, especially in Kepulauan Mentawai Regency, classified as a 3T area in West Sumatra province. The results provide valuable insights for stakeholders in choosing suitable production sites for frozen banana fritters, contributing to economic improvement in the region.